2013
DOI: 10.1051/epjconf/20134501106
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Performance Investigation of Photovoltaic/Thermal (PV–T) System

Abstract: Abstract. Photovoltaic solar cells convert light energy from the sun into electricity. Photovoltaic cells are produced by semi-conducting materials to convert the energy into electricity and during this process heat is absorbed by the solar radiation. This heat causes a loss of electricity generation efficiencies. In this study, an experimental setup was designed and established to test two separate photovoltaic panel systems with alone PV and with water cooling system PV/T to examine the heat effect on PV sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Although solar energy harvesting using solar cell technology is highly promising, there are challenges to maximizing the efficiency of solar cells [8][9][10]. PV modules based on silicon material can convert 8-20% of solar radiation into electrical energy [11][12][13] but the rest of the solar radiation is reflected back to the surrounding environment and converted into heat energy that can increase the temperature of the PV device and consequently reduce the total power output [14][15][16]. Radziemska [12] adjusted the working temperature of solar cells and showed an inverse linear relationship between the temperature and the power output of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although solar energy harvesting using solar cell technology is highly promising, there are challenges to maximizing the efficiency of solar cells [8][9][10]. PV modules based on silicon material can convert 8-20% of solar radiation into electrical energy [11][12][13] but the rest of the solar radiation is reflected back to the surrounding environment and converted into heat energy that can increase the temperature of the PV device and consequently reduce the total power output [14][15][16]. Radziemska [12] adjusted the working temperature of solar cells and showed an inverse linear relationship between the temperature and the power output of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The depletion region present between the two layers of semiconductor separates the charge carriers before recombination, which are collected with the help of electrodes, thereby producing the electric current. However, only 10% to 20% of the incident solar radiation can be converted into electric current using commercially available solar cells and the rest is dissipated as heat energy …”
Section: Introductionmentioning
confidence: 99%
“…Whittaker 8 showed that the temperature coefficients can be considered constant over the normal operating temperature range of the modules. Sun et al 9 used the finite element technique to demonstrate that irradiance and wind speed are important parameters for determining the temperature of the module Literature review shows one study 10 which demonstrates the impact of water cooling on the module efficiency due to the temperature decreasing. In other paper 11 the author proposes a simplified and practical way to polycrystalline module temperature calculation from the method of balance of energy.…”
Section: Introductionmentioning
confidence: 99%